Optimal sensor location for adaptive control system in tropical smart greenhouse - Folkes Eduard Laumal; Herry Suhardiyanto; Mohamad Solahudin; Slamet Widodo (Institute of Advanced Engineering and Science, 2023)
The uniform control in greenhouse with technology capabilities is seemingly still difficult to be obtained due to the accuracy uncertainty of the data in certain locations. Considering this case, it is highly necessary to choose the right location for the sensor installation. This study aimed to determine sensor placement locations to support precision control activities, using an arch-type smart greenhouse measuring 8×24 m2 as the research location. Air temperature was calculated from 12 locations and analyzed for all possible combinations to designate the best sensor point according to the number of sensors. The analysis was conducted using the error-based method to ascertain the number and location of sensors that represent the smart greenhouse. The best location and number of sensors are identified with performance value under 10% and recommended for developing an adaptive control system.